MADRASAH STRATEGY IN IMPROVING NUMBER OF STUDENTS (Study at MAN 4 Pandeglang) - Setiawan, Iwan (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
Madrasas are educational institutions that have an important role in providing religious and moral education to students. One of the main challenges faced by madrasas is increasing the number of students. This research aims to identify strategies that can be used by madrasas to increase the number of students. This research uses qualitative research methods by conducting interviews and observations of several madrasas as research samples. The research results show that there are several strategies that can be used by madrasas to increase the number of students, including; Improving the Quality of Education, Marketing and Promotion, Collaboration with the Community, Extracurricular Programs, Scholarships and Financial Assistance By implementing these strategies, madrasas can increase the number of their students, so that they can be more effective in providing religious and moral education to the younger generation. Further research can be conducted to measure the effectiveness of each of these strategies in increasing the number of madrasah students.